Desenho da gestão ambiental em municípios de pequeno porte do semiárido nordestino: o caso da cidade de independência - Mesquita, Maria do Socorro Silva (2010)
It presents a design of environmental management in a small city in the Northeast semi-arid, considering the perspective of environmental sustainability, economic and social development. The conceiving of the design of public environmental management passes through a process of upgrading the site, to recognize and understand the strengths and weaknesses inherent in semi-arid region, allowing actors and institutions involved develop skills for strategic definition of mitigation and adaptation to vulnerability of the semi-arid region. There is the inclusion of new actors into the process of decentralization of public management of the state to the city, identifying the main difficulties in the development of environmental management in the municipality. A major focus is proposed how to configure the instruments of environmental management adopted in the city through the work of local and perception of civil society representatives. Another contribution of this work is to build a set of sustainability indicators to track environmental performance. The research is qualitative and descriptive. For this, we carried out a depth theoretical research, and fieldwork in form of case studies, in wich the city of Independência/ CE was the unit of analysis. Data collection through semi-structured interviews were conducted with 29 key actors, representatives of government and civil society. The evidence permitted to describe the environmental management of the city of Independence, to understand the articulations of local and state government to promote sustainable development, reducing the negative impacts to the environment. Prevails in the environmental management sector in the city of Independência/ CE a defensive conceiving and sectorial design, where integration is partially possible.